Covid-19 lockdown and physical distancing policies are elitist: towards an indigenous (Afro-centred) approach to containing the pandemic in sub-urban slums in Nigeria. Issue 8 (2nd August 2020) - Iwuoha, Victor Chidubem; Aniche, Ernest Toochi
ABSTRACT: This study explores the experience of the sub-urban slum residents in Okpoko (Anambra State), Ngwa-road Aba (Abia State), Ajegunle (Lagos State) and Gwagwalada (Abuja), to underscore the elitist and western contexts of Covid-19 lockdown and physical distancing policies. The study apprehends these policies as being counter-productive due to Nigeria's peculiar socio-economic circumstances, and brainstorms on the need and prospects for adaption and institutionalisation of an indigenous Afro-centred approach towards the containment of the Covid-19 pandemic. The use of herbal mixtures or local concoctions such as parboiled garlic cloves, lemon and ginger juice in the treatment and/or prevention of Covid-19 pandemic is a popular home-grown indigenous approach/practice which is generally believed to have inhibitory effects against Covid-19 by majority of the local people. These herbal remedies should be formally investigated, validated and encouraged in Nigeria as an alternative indigenous approach for the prevention and treatment of Covid-19 pandemic.